2021
DOI: 10.1017/s0007114521000593
|View full text |Cite
|
Sign up to set email alerts
|

Insufficient iodine nutrition may affect the thyroid cancer incidence in China

Abstract: Epidemiologic studies have focused on the effects of iodine intake on the risk of thyroid cancer. However, their relationship is still obscure. The objective of this study was to examine the association in the Chinese population. A new ecological study which combined the Annual Report of Cancer, the Survey of Iodine Deficiency Disorder Surveillance and the water iodine survey were conducted to analyze the relationship between iodine intake and the thyroid cancer incidence in China. In total, 281 counties were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In 2019, out of 233,846 new cases and 45,575 deaths globally, China accounted for 16.71% and 15.88%, respectively [ 15 ]. The elevated prevalence of thyroid cancer in specific regions within China is potentially attributable to mild iodine deficiency [ 16 ]. Notably, regions such as Guangdong, Zhejiang, and Jiangsu have witnessed high incidence rates particularly among women, with variances of up to 45-fold between the least and most affected areas.…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, out of 233,846 new cases and 45,575 deaths globally, China accounted for 16.71% and 15.88%, respectively [ 15 ]. The elevated prevalence of thyroid cancer in specific regions within China is potentially attributable to mild iodine deficiency [ 16 ]. Notably, regions such as Guangdong, Zhejiang, and Jiangsu have witnessed high incidence rates particularly among women, with variances of up to 45-fold between the least and most affected areas.…”
Section: Resultsmentioning
confidence: 99%
“…However, radical thyroidectomy is difficult and prone to many postoperative complications. In addition, due to the pathological consumption of thyroid cancer, dysphagia symptoms, surgery and inflammation, a large amount of proteins and fats are consumed in the body, and patients may suffer from malnutrition status ( 15 , 16 ). One study ( 17 ) showed that patients with nutritional risk have a significantly higher incidence of postoperative infectious complications and a significantly longer hospital stay, so clinical workers need to pay attention to nutritional screening of surgical patients and the prognostic impact of nutritional risk on surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the thyroid gland is a potent collector of iodine, 34 and both insufficient and excessive iodine intake can result in thyroid diseases and even exert an impact on TC, indicating that sustaining proper iodine nutrition may help lower the incidence of TC. 35 Interestingly, because of different attenuation coefficients of the same substance at different energy X-rays, dual-energy CT scanning technique not only easily distinguishes iodine from other different substances but also accurately and quantitatively calculates the IC in the region of interest. 17 Through DSCT scanning, our results unveiled lower levels of IC in plain CT and venous phase NIC in TC patients than those in patients with benign lesions.…”
Section: Discussionmentioning
confidence: 99%